Use of an Absorbable Urethral Stent for the Management of a Urethral Stricture in a Stallion. Issue 8 (25th August 2016) - Trela, Jan M.; Dechant, Julie E.; Culp, William T.; Whitcomb, Mary B.; Palm, Carrie A.; Nieto, Jorge E.
Abstract : Objective: To describe the successful management of a urethral stricture with an absorbable stent in a stallion. Study Design: Clinical report. Animals: Stallion with a urethral stricture. Results: A 12‐year‐old Thoroughbred breeding stallion was evaluated for acute onset of colic. Uroperitoneum because of presumptive urinary bladder rupture, with urethral obstruction by a urethrolith, was diagnosed. The uroperitoneum was treated conservatively. The urethrolith was removed through a perineal urethrotomy. Approximately 15 weeks after urethrolith removal, the stallion presented with a urethral stricture. The stricture was unsuccessfully treated with an indwelling urinary catheter and 4 attempts at balloon dilation. Eight weeks after diagnosis of stricture, an absorbable polydioxanone (20 mm × 80 mm) urethral stent was implanted under percutaneous, ultrasound guidance. Urethroscopy was performed at 70, 155, and 230 days after stent placement and the endoscope passed through the affected site without complication. Urethroscopy at 155 days showed the stent had been reabsorbed. Follow‐up 20 months after stent placement reports the stallion was able to void a normal urine stream. Conclusions: Absorbable urethral stent placement was a feasible treatment for urethral stricture in this stallion.